The will to change ebook Men, masculinity, and love. - hooks, bell (2003)
From New York Times bestselling author, feminist pioneer, and cultural icon bell hooks, a timelessly necessary treatise on how patriarchy and toxic masculinity hurts us all, with a new introduction by poet Ross Gay. Feminist writing did not tell us about the deep inner misery of men. Everyone needs to love and be loved—including men. But to know love, men must be able to look at the ways in which patriarchal culture keeps them from understanding themselves. In The Will to Change , bell hooks provides a compassionate guide for men of all ages and identities to understand how to be in touch with their feelings, and how to express versus repress the emotions that are a fundamental part of who we are. With trademark candor and fierce intelligence, hooks addresses the most common concerns of men, such as fear of intimacy and loss of their patriarchal place in society, in new and challenging ways. The Will to Change "creates space for men to acknowledge their traumas and heal—not only for their sake, but for the sake of everyone in their lives" ( BuzzFeed ).